Interrogating Europe's voids of memory: trauma theory and Holocaust Remembrance between the National and the Transnational - Allwork, Larissa (Fondazione Centro di Documentazione Ebraica Contemporanea, 2016)
Reflecting on the research process for Holocaust Remembrance between the National and the Transnational (HRNT), which explores and analyzes the significance of the European and global politics of the commemoration of the Holocaust and Nazi-era crimes in the late 1990s and 2000s, this article will consider the influence of the intellectual context of trauma theory for this book. It will offer a response to the increasing critique of Eurocentric trauma theory which developed during the period spent researching the Stockholm International Forum (SIF 2000) and the first decade of the Task Force for International Co-operation on Holocaust Education, Remembrance and Research (ITF, now the International Holocaust Remembrance Alliance, IHRA). This article will discuss how a revised trauma theory, along the lines suggested by scholars such as Joshua Pederson, continues to offer important possibilities for European studies of the histories and memories of the Holocaust in singular and comparative terms.